Clinicoepidemiology and treatment outcome of acute intestinal obstruction in adult in KIMS Amalapuram: a retrospective observational study - Lakshmi, Y. Anantha; Narasimha Reddy, K. V. (International Surgery Journal, 2020)
Background: The intestinal obstruction is a common potentially risky surgical emergency in all age group globally. This is responsible for 12% to 15% of surgical admission due to acute abdomen. Obstruction to gastrointestinal tract can occur at all labels but it is small intestine which more commonly involved. To improve the outcome early diagnosis and management is essential. Present study has been designed to study the epidemiology, demography and clinical presentation of acute intestinal obstruction and to study the complications and outcome of surgical management of acute intestinal obstruction. Methods: In present study patients admitted with diagnosis of acute intestinal obstruction during study period were enrolled for this study as per inclusion and exclusion criteria. As per that 126 patients were enrolled for this study. Case record of all patients were closely reviewed and analysed thoroughly. Results: The mean age of the patients was 54.64±12.93 years. The acute intestinal obstruction was more common in 41 to 60 years of age group that is (44.45%). Regarding etiology of acute intestinal obstruction 44.45% patient adhesion was the etiology of obstruction. Resection of adhesion was most common procedure done for removal of obstruction (42.85%). Conclusions: Adhesion was most common etiology and pain abdomen and tachycardia was common presentation. Regarding management of obstruction resection of adhesion was most common procedure done for removal of obstruction. Infection of wound was common complication.